Trichome morphology of Durio zibethinus L - Shamin Shazwan, Kamaruddin; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Ghazali, Muhammad Zulkifli; Go, Rusea (Microscopy Society of Malaysia, 2020)
Knowledge regarding taxonomy such as plant species trichome morphology has developed significantly in recent years, which deals with the classification of an organism according to its similarity and variance. It offers vitally important knowledge for most plant classification systems, such as Durian varieties. The Durian is one of Malaysia's famous and sought after fruits. Therefore, this taxonomic study will serve as a complementary tool to the D. zibethinus variation assessment. Hence, this research was aimed at scrutinizing the trichome morphology variation of D. zibethinus. Samples of D. zibethinus leaves were collected from Jelebu, Negeri Sembilan and Jabatan Pertanian Bukit Goh, Kuantan, Pahang and kept as herbarium vouchers. Observation on trichome morphology was carried out by using a light microscope. The analysis revealed variations of trichome morphology in terms of its presence, morphological characteristics and trichome types. On the upper and lower surfaces of the D. zibethinus leaves, non-glandular trichome (lepidote trichome, stellate trichome, and simple trichome) is densely covered. Glandular trichome does not present in all accessions. To sum up, trichome morphology may be used in D. zibethinus identification process.